Extended pathology reporting of resection specimens of colorectal liver metastases: the significance of a tumour pseudocapsule. Issue 9 (27th December 2012) - Wiggans, Matthew G.; Shahtahmassebi, Golnaz; Malcolm, Paul; McCormick, Frances; Aroori, Somaiah; Bowles, Matthew J.; Stell, David A.
Abstract Introduction The aim of this study was to analyse the influence of factors reported in the minimum histopathology dataset for colorectal liver metastases (CRLM) and other pre‐operative factors compared with additional data relating to the presence of tumour pseudocapsules and necrosis on recurrence 1 year after a resection. Methods For a period of 14 months, extended histological reporting of CRLM specimens was performed, including the presence of pseudocapsules and necrosis in each tumour. The details of recurrence were obtained from surveillance imaging. Results In 66 patients there were 27 recurrences within 1 year. The rates were lower for patients with tumour pseudocapsules (8/27) than for patients without (19/36) (P = 0.030). Pseudocapsules were associated with a younger age (P = 0.005), nodal stage of the primary colorectal tumour (P = 0.025) and metachronous tumours (P = 0.004). In patients with synchronous disease and pseudocapsules, the recurrence rate was 2/12 compared with 13/23 patients without pseudocapsules (P = 0.026). Discussion These findings demonstrate that histological examination of resection specimens can provide significant additional prognostic information for patients after resection of CRLM, compared with clinical and radiological data. The present finding that the absence of a pseudocapsule in patients with synchronous CRLM is associated with a dramatically worse outcome may help direct patient‐specific adjuvant treatment and care.